ASTHENOPIA SEBAGAI DAMPAK INTERNET GAMING DISORDER: STUDI TERHADAP REMAJA DI YOGYAKARTA - GITA DIAH PRASASTI (JURNAL ILMIAH KOHESI, 2023)
Internet Gaming Disorder (IGD) has become a social issue that has been researched in large number in recent years, especially in relation to the health issues. High exposure to electronic screens for playing video games is prone to failure of adaptation and plasticity of the visual system so that asthenopia symptoms and changes in visual function can occur. This study aims to determine the relationship between IGD and asthenopia in adolescents in Yogyakarta. The subjects of this cross-sectional study were adolescents in the Special Region of Yogyakarta Province. The instruments used in this study were the Indonesian version of the Game Addiction Scale-7 questionnaire (GAS-7 Ina) to identify IGD, as well as the Computer Vision Syndrome questionnaire to assess asthenopia symptoms. Analysis was later performed to determine the relationship between the IGD and asthenopia. We obtained 110 adolescents that consist of 55 IGD subjects and 55 non IGD subjects with a mean age of 13.9 ± 0.5 years old. Bivariate and multivariate analysis showed that IGD had a significantly related to asthenopia (p=0.019) with OR 4.08. The distance to the electronic screen <40cm was increased the risk of developing asthenopia (p=0.045) with OR 2.35. Internet gaming disorder (IGD) is independently associated with asthenopia. The distance to the electronic screen and the screen exposure time (the duration of playing games) were also factors that can increase the risk of developing asthenopia in adolescents with IGD.